The Impact of Using Live Streaming E-Commerceon Urge to Buy Impulsively - Nadya Amanda Putri Diego; Anas Hidayat (Universitas Negeri Semarang, 2025)
This research aims to explore the factors that drive impulsive buying during e-commerce live streaming though the Stimulus-Organism-Response (S-O-R) theory. The study was distributed to 290 respondents who are users of Shopee and TikTok platforms and have made purchases during live streaming, using purposive sampling in non-probability sampling and utilizing Google Forms for data collection. Data analysis was conducted quantitatively and processed using PLS-SEM with the SmartPLS 3.0 software. The findings reveal that trustworthiness and expertise positively and significantly influence perceived enjoyment, while purchase convenience and product price positively and significantly influence perceived usefulness. Additionally, perceived enjoyment and perceived usefulness positively and significantly affect the urge to buy impulsively. This indicates that live streaming can enhance consumers’ impulsive buying behavior. This study contributes by providing insights for e-commerce platform developers, businesses, managers and marketing teams to leverage the potential of e-commerce live streaming in this evolving digital era.